Central African Republic : Request for Disbursement Under the Rapid Credit Facility and Cancellation of the Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Central African Republic's (CAR) Request for Disbursement Under the Rapid Credit Facility (RCF) and Cancellation of the Extended Credit Facility Arrangement. The transitional government in CAR is facing daunting challenges. Improved security, donor support, and normalizing salary payments will be crucial to start a recovery in 2014. The macroeconomic outlook is subject to uncertainty and risks. The IMF staff supports the authorities' request for assistance under the RCF in view of their currently limited capacity to implement policies of an upper credit tranche-quality economic program, the large and urgent balance-of-payments needs, and the catalytic effect of IMF support on other external assistance.